The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1007/s001040050878
|View full text |Cite
|
Sign up to set email alerts
|

Heparininduzierte Thrombocytopenie Typ II

Abstract: Heparin-induced thrombocytopenia type II (HIT type II) is an immunoglobulin-mediated, drug-induced side effect for heparin-treated patients with thromboembolic complications. With an incidence of 1-3 %, mortality of 20 % it and permanent disability for another 20 % is a clinically relevant disorder. With heparin treatment or prophylaxis frequent platelet count monitoring is necessary. With HIT type II the thrombocytopenia is often a harbinger of thromboembolic complications in the venous or arterial system. If… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
1
0
2
Order By: Relevance
“…Die HIT II stellt mit einer Inzidenz von 0,5 ± 3 % eine seltene, jedoch potenziell lebensgefährliche Komplikation unter Heparintherapie dar [1,3,4]. Sie tritt typischerweise 5 ± 14 Tage nach Beginn der Heparingabe auf, selten erst nach der 3.…”
Section: Abbunclassified
“…Die HIT II stellt mit einer Inzidenz von 0,5 ± 3 % eine seltene, jedoch potenziell lebensgefährliche Komplikation unter Heparintherapie dar [1,3,4]. Sie tritt typischerweise 5 ± 14 Tage nach Beginn der Heparingabe auf, selten erst nach der 3.…”
Section: Abbunclassified
“…Die optimale Dauer einer NMH-Prophylaxe ist bisher nicht schlüssig geklärt (10,12,18,19), so fand Hagmüller (11) wie auch wir thromboembolische Komplikationen Tage bis Wochen nach Varizenoperationen. Wenn man nun die Dauer der NMH-Prophylaxe verlängert (2), muß man aber auch mit der Zunahme der heparinassoziierten Komplikationen (7,8,16,21) rechnen. Wir sind der Ansicht, daß zumindest bei Patienten ohne besonderes Thromboserisiko auf eine zusätzliche medikamentöse Thromboseprophylaxe mit NMH in der Varizenchirurgie verzichtet werden kann (15).…”
Section: Diskussionunclassified
“…For several years, in addition to frequent bleeding, immunologically related heparin-induced thrombocytopenia (HIT type II) has become increasingly important as a severe complication. There is a lack of prospective studies, but the incidence has been reported to range from 0.9% to 3.3% [1,2,3,4,5]. It is because of both the degree of sulfation and the molecular weight that the occurrence of HIT has been more frequent with UFH than with the low-molecularweight heparins (LMWH; 7.8% versus 2.2%, of which symptomatic cases have been reported at 2.7% versus 0% [6,7]).…”
Section: Introductionmentioning
confidence: 99%